An Analysis of Teachers’ Nonverbal Communication in EFL Classroom Interaction - Wahyuni, Sry; Usman, Misnawaty; Samad, Ita Sarmita; As'ary, Muawwal Al (ARRUS Journal of Social Sciences and Humanities, 2025)
Nonverbal communication (NVC) plays a crucial role in the teaching and learning process, especially in facilitating students’ understanding and engagement. However, its use sometimes is overlooked by the teacher. Therefore, this study aimed to analyze the kinds of NVC used by teachers in classroom interaction. It used qualitative research. Two EFL lecturers were chosen as the subject of this study. It was held at the Undergraduate Program of the English Education Department of Universitas Negeri Makassar. Observation checklists and classroom observations were used to gather the data. The interactive model of data analysis technique, which includes data collecting, data display, data condensation, and conclusion-drawing or verification, was used to analyze the observational data. The findings revealed that all kinds of NVC were utilized by the teachers. It included the use of gesture, movement, facial expression, eye contact, touch, and distance. It is intended that this study will help the teachers, especially English teacher to improve their communication skills by utilizing nonverbal communication in classroom interaction.